Physiological Response and Production Ability of Beef Cattle Raised Based on Different Altitudes in Sinjai Regency - Hermawansyah Hermawansyah; Bahri Syamsuryadi; Iin Mutmainna (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2021)
The breeders' knowledge of the suitability of the breeding environment for cattle breeds may increase livestock productivity. Determining the differences in microclimate environmental conditions, physiological responses, and production capabilities of Bali and Limousine crossbred cattle raised at different altitudes in Sinjai Regency were the aim of this study. The research was carried out on people's farms in Sinjai, which were divided into three locations based on the height of different rearing places; low areas (0-100 masl) were represented by East Sinjai sub-district, South Sinjai sub-district for medium plains areas (100-400 masl), and highland areas (>400 masl) were represented by West Sinjai sub-district. The selection was based on the height of the place and beef cattle business in the area. The materials used were 30 Balinese cattle and 24 Limousine hybrids. This research was conducted from July to September 2020. The method of the research used direct observation in the field. Data collection used the method of direct observation in the field. The parameters observed were; microclimate conditions, physiological responses, and beef cattle production capabilities. The research found that the altitude of keeping Bali cattle and Limousine breeding affected the microclimate conditions such as air temperature and humidity in the highlands. The air temperature is lower in the highlands but the humidity is higher than the lowlands. Besides, on the physiological response parameters, the altitude effected on the Limousine hybrid as well as respiratory frequency and pulse rate of Bali cattle. Respiratory and pulse rates are lower at high altitudes. The height of the breeding ground also affected the height of the Bali cattle, and the chest circumference of the Limousine hybrid.Â